The Interactional Features of Billingual Teacher Talk in the Classroom of Arabic as a Foreign Language - Basyori, Ahmad; Asrori, Imam; Sutaman, Sutaman; Ahmed, Bakri Mohamed Bkheet (Universitas Islam Negeri Raden Intan Lampung, 2021)
Communication is essential in studying Arabic as a foreign language to make the lesson interactive. This research aimed to identify and assess three aspects. First, the Teacher Talk (TT) interaction feature appeared in the Arabic Education Study Program, Faculty of Tarbiyah and Teacher Training, Raden Intan State Islamic University of Lampung. Second, each lecturer's primary type of TT interaction element. Third, the utilization of code-switching as a component of bilingual learning interactions. This research was a case study of three Arabic lecturers (T1, T2, and T3) who used Google Meets to conduct online learning. Each lecturer was videotaped three times and then examined using Miles and Huberman's qualitative approach. The findings of the L2 investigation demonstrate that 1) T1 produced twelve different types of interaction features. Furthermore, T2 produced eleven different types of interaction features. Finally, T3 produced twelve different types of interaction features. 2) The most dominant TT interaction features in the classrooms by T1 was Scaffolding (18.2 percent), T2 was Display Questions (24.6 percent), and T3 was Confirmation Check (23.1 percent). 3) In the context of bilingual classes, this study also found that L2 lecturers used other interaction features to facilitate interaction, namely code-switching from Arabic (L2) to Indonesian (L1) and vice versa. The total occurrence of code-switching by T1 was 9.1 percent (the least), code-switching by T2 was 27.3 percent, and code-switching by T3 was 63.6 percent (the most dominant). Code-switching can be an excellent alternate approach or interaction tool for facilitating communication in the classroom when learning Arabic; nevertheless, it must be used appropriately and proportionally.